PENGARUH EDUKASI, SOSIALISASI DAN PEMAHAMAN PERATURAN PEMERINTAH NO 46 TAHUN 2013 DAN NO 23 TAHUN 2018 TERHADAP KEPATUHAN WAJIB PAJAK : Studi Empiris Pada UMKM Di Sentra Industri Tenun Kecamatan Ibun Kabupaten Bandung - Dudi Sudirman; Edih A. Hamid; Achmad Subagdja; Iwan Setiawan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study was to determine the effect of education, socializationand understanding of Government Regulation no. 46 of 2013 and No. 23 of2018 Against Taxpayer Compliance. The research method used in this researchis descriptive and verification method using a quantitative approach, where thedata obtained from the research sample is analyzed according to the statisticalmethod used and then interpreted rationally and accurately. Furthermore, it isanalyzed using correlation coefficient analysis, coefficient of determination,multiple regression and hypothesis analysis with t test and F test. The resultsobtained by the value of the coefficient of determination (R2) of 0.806 meansthat 80.6% of the taxpayer compliance variable can be explained by education,socialization and understanding of government regulation no. 46 of 2013 andNo. 23 of 2018, which can also mean that taxpayer compliance can beexplained by education, socialization and understanding of governmentregulation no. 46 of 2013 and No. 23 of 2018 has a strong effect on taxpayercompliance, it can also be interpreted that the influence of variables outside themodel or other factors is 19.4%. Based on the results of the hypothesis test, asignificance level of 0.000 was obtained when compared to an alpha of 0.05,the significance level is smaller than alpha, so the hypothesis can be accepted,meaning that there is an influence of education, socialization of tax regulationsand understanding of government regulations no. 46 of 2013 and No. 23 of2018 on taxpayer compliance in the SMEs of the Weaving Industry Center,Ibun District, Bandung Regency